2021
DOI: 10.1016/j.jcjp.2021.100011
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression and histological studies of articular chondrocytes in cam-type femoroacetabular impingement demonstrates chronic and sustained inflammation and age related abnormal extracellular matrix

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…While we observed increased expression of these markers in the OA compared to the total FAI cohort on the sequencing arm of this study, subsequent validation with qRT‐PCR found similar expression between high‐grade FAI and osteoarthritic cartilage, suggesting that expression of inflammatory markers increases as FAI progresses towards OA. These findings were supported in a recent study by Liang and colleagues who found differences in COL2A1, ACAN, and MMP3 immunostaining between early and late‐stage FAI samples 18 . Taken together, these results suggest that as the degenerative processes of FAI become more advanced the articular cartilage expression profile parallels that of osteoarthritic cartilage.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…While we observed increased expression of these markers in the OA compared to the total FAI cohort on the sequencing arm of this study, subsequent validation with qRT‐PCR found similar expression between high‐grade FAI and osteoarthritic cartilage, suggesting that expression of inflammatory markers increases as FAI progresses towards OA. These findings were supported in a recent study by Liang and colleagues who found differences in COL2A1, ACAN, and MMP3 immunostaining between early and late‐stage FAI samples 18 . Taken together, these results suggest that as the degenerative processes of FAI become more advanced the articular cartilage expression profile parallels that of osteoarthritic cartilage.…”
Section: Discussionsupporting
confidence: 80%
“…Several studies have evaluated the expression of inflammatory markers isolated from pathologic tissues in FAI and hip OA (Table 1). [7][8][9][10][11][12][13] In a preliminary study of articular cartilage harvested during cam resection for FAI compared to articular cartilage from osteoarthritic hips, Hashimoto et al reported increased expression of inflammatory mediators and markers of cartilage turnover (IL8, ADAMTS4, ACAN). 7 In a subsequent study, Chinzei et al 7 confirmed increased expression of inflammatory markers in FAI cartilage compared to OA, while OA labral and synovial samples had higher levels of inflammation compared to FAI.…”
mentioning
confidence: 99%
“…These findings were supported in a recent study by Liang and colleagues who found differences in COL2A1, ACAN, and MMP3 immunostaining between early and late-stage FAI samples. 12 Taken together, these results suggest that there are both etiologic and temporal factors impacting gene expression between FAI and osteoarthritic cartilage, and as the degenerative processes of FAI become more advanced the articular cartilage expression profile parallels that of osteoarthritic cartilage.…”
Section: Discussionmentioning
confidence: 63%
“…Differential expression for previously identified markers in FAI and OA [6][7][8][9][10][11][12]. *indicates increased expression in OA compared to FAI.…”
mentioning
confidence: 99%